Genetic interaction of DISC1 and Neurexin in the development of fruit fly glutamatergic synapses. (December 2017) - Pandey, Himani; Bourahmoune, Katia; Honda, Takato; Honjo, Ken; Kurita, Kazuki; Sato, Tomohito; Sawa, Akira; Furukubo-Tokunaga, Katsuo
Abstract Originally identified at the breakpoint of a (1;11)(q42.1; q14.3) chromosomal translocation in a Scottish family with a wide range of mental disorders, theDISC1 gene has been a focus of intensive investigations as an entry point to study the molecular mechanisms of diverse mental dysfunctions. Perturbations of theDISC1 functions lead to behavioral changes in animal models, which are relevant to psychiatric conditions in patients. In this work, we have expressed the humanDISC1 gene in the fruit fly (Drosophila melanogaster ) and performed a genetic screening for the mutations of psychiatric risk genes that cause modifications ofDISC1 synaptic phenotypes at the neuromuscular junction. We found thatDISC1 interacts withdnrx1, theDrosophila homolog of the humanNeurexin (NRXN1 ) gene, in the development of glutamatergic synapses. While overexpression ofDISC1 suppressed the total bouton area on the target muscles and stimulated active zone density in wild-type background, a partial reduction of thednrx1 activity negated theDISC1 –mediated synaptic alterations. Likewise, overexpression ofDISC1 stimulated the expression of a glutamate receptor component, DGLURIIA, in wild-type background but not in thednrx1 heterozygous background. In addition, DISC1 caused mislocalization of Discs large, theDrosophila PSD-95 homolog, in thednrx1 heterozygous background. Analyses with a series of domain deletions have revealed the importance of axonal localization of the DISC1 protein for efficient suppression of DNRX1 in synaptic boutons. These results thus suggest an intriguing converging mechanism controlled by the interaction ofDISC1 andNeurexin in the developing glutamatergic synapses. Genetic risk factors: Mapping interaction in fruit flies Fruit fly models uncover a potential new mechanism by which two schizophrenia risk factor genes interact to alter synaptic junctions. DISC1 gene alterations have previously been linked to psychiatric anomalies, although the gene has not been formally recognized as a schizophrenia risk factor. A US-Japan research collaboration led by the University of Tsukuba's Katsuo Furukubo-Tokunaga expressed human DISC1 in fruit fly synapses to better understand the changes that take place when gene disruption leads to overexpression. The team found that overexpression of DISC1 affected the expression of the fruit fly counterpart to human 'neurexin, ' a known risk factor for conditions including schizophrenia and autism spectrum disorders. The interaction between neurexin and DISC1 also influenced other synapse-altering genes. Further research is warranted to explore the roles of DISC1 and neurexin in psychiatric disease.